ANALISIS NILAI TAMBAH PEMANFAATAN INDIGOFERA SEBAGAI BAHAN PEWARNAALAMI BATIK TULIS DI KECAMATAN IMOGIRI KABUPATEN BANTUL - Stefani Nurmavianti; Masyhuri Masyhuri; Dwijdono Hadi Darwanto (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2015)
Indigofera is one of natural dyes which is used in batik. Value added of agricultural products can incrase economic growth. The aims of this research were to: (1) determine the value added of indigo paste, batik tulis blue indigo, and blue combination; (2) determine the magnitude of average value added batik tulis blue indigo and blue combination; (3) determine the factors that influence to value added of batik tulis blue indigo and blue combination; (4) identify the obstaclesfaced by producers and how to overcome them. This research was conducted in Imogiri Subdistrict Bantul Regency. There were ten samples of batik tulis producers which was obtained by census method, while the producers of indigo paste were two samples which was obtained by snowball sampling. Then the data were analyzed using Hayami method, independent samples t-test, and multiple linear regression. The results showed that value added of indigo paste was low Rp1.643,00Ikg of leaves (38,66%), both batik tulis blue indigo and blue combination had high value added, they were Rp351. 713, 35/piece of plain cloth (68,39%) and Rp 399.428, 45/piece of plain cloth (70,23%). Be sides, natural dyes of textile also had value added in environment and health. The average of value added batik tulis blue indigo was lower than blue combination, but did not differ significantly. The factor that positive influenced significantly to value added ofblue indigo and blue combination batik tulis was price of batik. The factors that negative influenced significantly to value added of blue combination batik tulis were cost of indigo paste and other natural dyes. The factors that influenced to value added of batik tulis blue indigo and blue combination together were price of batik tulis that influenced positive significantly, cost of activation material that influenced negative significantly, and dummy colours influenced negative significantly. The main obstacles facing producers of batik tulis indigo and indigo paste were marketing, continuity of indigo paste, colouring techniques was difficult, a few profit, and the quality ofindigofera s leaves.